MACROFUNGI INVENTARITATION AT THE PINE FOREST OF KRAGILAN, MAGELANG - Nita Noviyanti; Wahyu Aji Mahardhika; Arina Tri Lunggani; Ivan Permana Putra (BIOVALENTIA: Biological Research Journal, 2022)
The pine forest of Kragilan village, Magelang, is a forested area on the west slopes of Mount Merbabu with a humid environmental condition. The conditions make this region suitable for the growth of a macrofungal community. The macrofungal inventory in Merbabu Mountain is very limited and this is inversely proportional to the increasing deforestation. Thus, the macrofungal inventory is a fundamental way of managing natural conservation in this area. The study aimed to provide information and the potency of macrofungi found in the pine forest area of Kragilan, Magelang. The method used is purposive sampling in the research area, and the fungi obtained were identified based on characteristics with some related references. This research described eight species of eight different genera, including one from the Ascomycota (Xylaria sp.), and seven others from the Basidiomycota (Auricularia auriculajudae, Lentinellus sp., Mycena sp., Skeletocutis sp., Gymnopilus sp., Coprinopsis sp., and Coprinellus disseminatus). The current study is the first report on macrofungi diversity in the research area. Further exploration is still needed to record the macrofungal diversity on the western slopes of the Kragilan pine forest.